PTU-058 Frequency and characteristics of high-risk colorectal polyps in a non-tertiary endoscopic mucosal resection (EMR) service. (8th June 2018) - Rajendran, Arun; Braby, Thomas; Pomfret, Suzanne; Macfarlane, Bruce; Landy, Jonathan
Abstract : Introduction: Recent guidelines and published data of large colorectal polyps. 1 2 suggest polyp characteristics associated with an increased risk of submucosal invasive cancer (SMIC) which might be best managed with en bloc resection. Data regarding the frequency and characteristics of such lesions are limited outside of tertiary centres. Our endoscopy screening centre is a district general hospital (DGH) providing EMR service for a population of around 5 50 000. We aimed to evaluate the frequency of large colorectal polyps with an increased risk of malignancy to plan further service provision for these lesions in the DGH setting. Methods: The hospital endoscopy database was interrogated to identify all colorectal EMRs for large polyps (>20 mm) performed from Jan 2014–Sept 2017. The data was retrospectively audited for polyp size, site, Paris classification, histology and cancer risk factors. Results: A total of 239 lesions were identified over a 45 month period. 35 (15%) lesions were excluded from further analysis owing to lack of data on either size, Paris classification or histology. 204 lesions (183 patients) with complete data were further analysed. Of 183 patients, the mean age was 69, (M: F 105:99). The mean size of polyps was 32 mm. 144 (60%) were distal lesions. 17 (8%) lesions were found to have cancer in the resected histological specimen. Table 1 summarises the characteristics of the lesions analysed. The incidence of HGD and cancer were further analysed according to size, location and Paris classification. There were 41 polyps with HGD (22%) and 17 (8%) with SMIC in our cohort with most lesions being distal, 0–1 s and <40 mm. Table 2 summarises the histology (Group A and Group B) lesions according to site and Paris classification. Additionally, 69 (34%) lesions showed polyp characteristics associated with an increased risk of covert SMIC in previously published data (IIc or 0-Is, Is +IIa with distal location). 2 Conclusion: High-risk lesions (HGD/cancer) comprised 30% of the total cohort and those potentially associated with covert SMIC (IIc and distal Is/Is+IIa lesions) formed 34% of the cohort. From our data, up to 32 lesions per year may necessitate en bloc resection. 1 2 This audit has identified the need to plan for service provision in a DGH for large colorectal polyps including potential referral pathways to achieve en bloc resection of lesions with a higher potential for SMIC. Reference: . Rutter MD, et al. Gut2015. . Burgess N, et al. Gastro 2017.